2012
DOI: 10.1292/jvms.12-0063
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteins Regulated by Ferulic Acid in a Middle Cerebral Artery Occlusion Animal Model-A Proteomics Approach

Abstract: ABSTRACT. Ferulic acid plays a neuroprotective role in cerebral ischemia. The aim of this study was to identify the proteins that are differentially expressed following ferulic acid treatment during ischemic brain injury using a proteomics technique. Middle cerebral artery occlusion (MCAO) was performed to induce a focal cerebral ischemic injury in adult male rats, and ferulic acid (100 mg/kg) or vehicle was administered immediately after MCAO. Brain tissues were collected 24 hr after MCAO. The proteins in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…We previously demonstrated that ferulic acid contributes to the up- and down-regulation of various specific proteins during MCAO injury. Among these proteins, this study was focused on PP2A subunit B expression [16].…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that ferulic acid contributes to the up- and down-regulation of various specific proteins during MCAO injury. Among these proteins, this study was focused on PP2A subunit B expression [16].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that ferulic acid exerts a neuroprotective effect against MCAO injury by modulating several proteins [32]. Such as resveratrol, ferulic acid is a phenolic compound that extracted from plant.…”
Section: Discussionmentioning
confidence: 99%
“…2-Dimensional gel electrophoresis : Proteomic analysis was carried out as our previously described method [32]. Proteins were extracted from the right cerebral cortex by homogenization in buffer solution (8 M urea, 4% CHAPS, ampholytes and 40 mM Tris–HCl) followed by centrifugation at 16,000 g. Protein concentration was determined by the Bradford method (Bio-Rad, Hercules, CA, U.S.A.) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ferulic acid exerts potent protection against glutamate‐induced toxicity (Yu et al, ) and significantly reduces the infarct volume in a cerebral ischemic injury animal model. We previously demonstrated that ferulic acid plays a neuroprotective role against focal cerebral ischemia through the up‐ and down‐modulation of various proteins (Sung et al, in press).…”
Section: Introductionmentioning
confidence: 99%